Xanthophyll Cycle Activity in Two Prominent Arctic Shrub Species. Issue 2 (1st May 2017) - Magney, Troy S.; Logan, Barry A.; Reblin, Jaret S.; Boelman, Natalie T.; Eitel, Jan U. H.; Greaves, Heather E.; Griffin, Kevin L.; Prager, Case M.; Vierling, Lee A.
ABSTRACT: When the capacity for photosynthesis is constrained by unfavorable growing conditions, excess absorbed light is safely lost from leaves via thermal energy dissipation—a photoprotective mechanism ubiquitous among higher plants. The relatively low irradiance conditions yet stressful growing environment of the arctic tundra suggest contrasting hypotheses regarding the necessity for plant investment in photoprotection. To examine these hypotheses, the photoprotective pigments of the xanthophyll cycle were investigated in conjunction with non-photochemical quenching (NPQ) of chlorophyll fluorescence emission in two dominant arctic shrub species, Salix pulchra and Betula nana. The xanthophyll cycle pool sizes of S. pulchra leaves were substantially higher than those reported in most other higher plant species, whereas B. nana leaves maintain modestly high xanthophyll cycle pool sizes. In addition, high retention of de-epoxidized xanthophyll cycle pigments in both species and saturation of xanthophyll cycle conversion at low-light intensities were observed and associated with high levels of NPQ. The xanthophyll cycle leaf pigment pools reported are among the first published for arctic plants and support the hypothesis that foliar xanthophyll cycle activity is greater in environments prone to harsher growing conditions.